Estuarine biofilm patterns: Modern analogues for Precambrian self‐organization. Issue 5 (26th February 2020) - van de Vijsel, Roeland C.; van Belzen, Jim; Bouma, Tjeerd J.; van der Wal, Daphne; Cusseddu, Valentina; Purkis, Sam J.; Rietkerk, Max; van de Koppel, Johan
Abstract:  This field and laboratory study examines whether regularly patterned biofilms on present‐day intertidal flats are equivalent to microbially induced bedforms found in geological records dating back to the onset of life on Earth. Algal mats of filamentous Vaucheria species, functionally similar to microbial biofilms, cover the topographic highs of regularly spaced ridge–runnel bedforms. As regular patterning is typically associated with self‐organization processes, indicators of self‐organization are tested and found to support this hypothesis. The measurements suggest that biofilm‐induced sediment trapping and biostabilization enhance bedform relief, strength and multi‐year persistence. This demonstrates the importance of primitive organisms for sedimentary landscape development. Algal‐covered ridges consist of wavy‐crinkly laminated sedimentary deposits that resemble the layered structure of fossil stromatolites and microbially induced sedimentary structures. In addition to layering, both the morphological pattern and the suggested formation mechanism of the recent bedforms are strikingly similar to microbialite strata found in rock records from the Precambrian onwards. This implies that self‐organization was an important morphological process in times when biofilms were the predominant sessile ecosystem. These findings furthermore emphasize that self‐organization dynamics, such as critical transitions invoking ecosystem emergence or collapse, might have been captured in fossil microbialites, influencing their laminae. This notion may be important for paleoenvironmental reconstructions based on such strata. © 2019 The Authors. Earth Surface Processes and Landforms published by John Wiley & Sons Ltd Abstract : A field and laboratory study of algal biofilms promoting self‐organization of regularly spaced bedforms on present‐day intertidal flats. Biostabilization by algal mats stimulates ridge formation, multi‐annual persistence and thereby lamination in estuarine bedforms. Algal bedforms show striking similarity in morphology, lamination and governing processes to layered microbialites found in rock records from the Precambrian onwards, suggesting that similar self‐organization processes were important on early Earth, prior to the evolution of complex life.